Rock burst assessment and prediction by dynamic and static stress analysis based on micro-seismic monitoring - He, Jiang; Dou, Linming; Gong, Siyuan; Li, Jing; Ma, Zhiqiang (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2017)
A comprehensive analysis is conducted of the stress distribution and dynamic stress disturbance based on micro-seismic monitoring used to predict the rock burst risk zone according to the principle that a rock burst is induced by static stress concentration and dynamic stress disturbance.